(untitled) (Revista Música, 2020)
Interview with Brazilian pianist Sônia Rubinsky. The present interview contributed immensely to the interviewer's academic master's research (concluded on June 26, 2017), which aims to investigate the diversity of Ernesto Nazareth interpretations, whose music has been performed by classical pianists and choro groups.